Handel zagraniczny a zatrudnienie: sektorowa i regionalna analiza w odniesieniu do Niemiec i rozszerzonej Unii Europejskiej - Dieckheuer, Gustav (International Trade and Employment: A Sectoral and Regional Analysis for Germany and the EU25, 2006)
The point of reference of the paper is as follows: Germany (particularly) and other EU members, including the new ones (having entered the EU in 2004), are subject to the process that increased exports influence comparatively weaker the national income and employment level. This is mostly caused by high growth rates of labor productivities and increasing import intensities, in export sectors particularly. As far as new EU member countries are concerned, an additional factor is the whole transition process. Against this background, the author gives a broader analysis of national intersectoral links in Germany and of export-import links within the EU-25. Basing on a theoretical and empirical national input-output model for Germany and international export-import model for few country groups of the EU-25, this analysis attempts at answering some important questions concerning the relationship between exports and economic performance of Germany. These include, among other things, problems of sectoral changes in German exports and their bearing upon the GDP, value added and employment effects of increasing exports and the distribution of GDP, and employment effects of additional German exports among the EU countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 58-80